FosB mRNA Expression in Peripheral Blood Lymphocytes in Drug Addicted Patients - Anders, Quézia Silva; Klauss, Jaisa; Rodrigues, Livia Carla de Melo; Nakamura-Palacios, Ester Miyuki (Frontiers in Pharmacology, 2018)
FosB gene heterodimerizes with Jun family proteins to form activator protein 1 (AP-1) complexes that bind to AP-1 sites in responsive genes to regulate transcription in all cells. The genic expression of FosB seems to be modified after long time exposure to drugs of abuse and these changes may be involved in craving and addicted behavior. This study investigated the FosB mRNA expression in peripheral blood lymphocytes of drug addicted patients using real-time PCR approach. Thus, patients with crack-cocaine use disorder (CUD, n = 10), alcohol use disorder (AUD, n = 12) and healthy non-addicted subjects (CONT, n = 12) were assessed. FosB mRNA expression was reduced by 1.15-fold in CUD and 2.17-fold in AUD when compared to CONT. Hedge’s effect size gs over log FosB/Act was of 0.66 for CUD and of 0.30 for AUD when compared to controls. This study showed that FosB mRNA expression was detected in lymphocytes from peripheral blood for the first time, and it was less expressed in drug addicted patients. This molecular technique may constitute a potential peripheral marker for substance use disorder.